(3QDjI JMdjdjI fbOjIs - (3GSeGYjd Ydj(B, (3SYOs ((3GdGScfOQjI(B:s (3OGQ GdeYQaI GdLGeYjI(B,s, 2004)
(3aj gPG GdcJGH GdeLJeY , GdGJUGd , HfGA GdbhI aj GdeLJeY hGdGJUGd , GSJNOGeGJ eUWdM GdGOjhdhLjI , hSGFd GdGJUGd , GdQCj GdYGe , JYQja GdQCj GdYGe , GdOYGjI , GdacQ hCMhGdg GdGLJeGYjI , JTcjdI GdehGba hJZjjQgG , GdGjOjhdhLjI cYbjOI GbfGYjI hcfXQjI , OYhI GdGSdGe hGdGOjhdhLjIs
(3jHdjhZQGajG U(B. 465s
Keywords: (3G dQCj GdYGes; (3GdGJUGds; (3GdGYdGes; (3GdOYGjIs